2000
DOI: 10.1002/1098-2302(200011)37:3<144::aid-dev3>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory conditioning facilitates diet transition in human infants

Abstract: We evaluated whether Pavlovian conditioning methods could be used to increase the ingestion of non-preferred solutions by formula-fed human infants. In baseline measures, 5±7 month old infants sucked less frequently and consumed less water than regular formula. During a 3-day olfactory conditioning period, parents placed a small scented disk, the conditioned stimulus, on the rim of their infants' formula bottle at every feeding. Following this training, infants' responses to water were tested when their water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Interestingly, the enhanced consumption by restrained eaters was highly specific; those participants also showed greater consumption of cookies after the cookie cue than after the pizza or no cue. Given that cue-potentiated feeding has been observed in human infants [39] and young children [40], a better grasp of the determinants of this phenomenon may prove useful in understanding the development of both normal and pathological eating.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, the enhanced consumption by restrained eaters was highly specific; those participants also showed greater consumption of cookies after the cookie cue than after the pizza or no cue. Given that cue-potentiated feeding has been observed in human infants [39] and young children [40], a better grasp of the determinants of this phenomenon may prove useful in understanding the development of both normal and pathological eating.…”
Section: Discussionsupporting
confidence: 68%
“…Such early odour experience favours the emergence of human infants' selective responsiveness to foods [12,13,95,96]. That odour cues positively associated with human milk support infant acceptance of novel feeding contexts (bottle: [97]) or of novel foods [11] attests to the strength of these initial maternal olfactory effects. Third, beyond experience of dominant flavour qualities in amnio or in lacto, early and prolonged exposure to chemosensory variety induces weanlings to tolerate ingesting more of a food that is a priori repulsive because it is unusual.…”
Section: Odour-based Maternal Weaning Strategiesmentioning
confidence: 98%
“…Johnson et al (1991) demonstrated a preference for a flavor associated with higher energy density (FNL) in children aged 2–5 years. Coyle et al (2000) demonstrated that olfactory associative conditioning could be used to increase intake of water in 6-month-old infants (FFL). During three feeds, infants were exposed to a scented disc placed around the top of a bottle containing their regular, liked formula milk.…”
Section: Summary Of Literaturementioning
confidence: 99%